Having More Plants at Home During the Covid-19 Pandemic: Is It Just Following A Trend? - Whisnu Febry Afrianto; Rindang Diannita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The Covid-19 pandemic has drastically changed the social and environmental conditions. People should stay at home for self-isolation and social distancing to avoid the spread of Covid-19. People tend to have more plants at home associated with psychological impact during self-isolation. This study aimed to describe having more plants during the Covid-19 pandemic in Indonesia. A nationwide cross-sectional survey involving an online survey was carried out of an Indonesian population-based sample of 412 respondents from 26 provinces, considered demographic, social, and behavioral variables. The variable affecting the having plants during the Covid-19 pandemic was analyzed using non-parametric analysis of the Kruskal Wallis test. The result showed that people preferred having more plants during the Covid-19 pandemic to reduce negative emotions and feelings. The majority of the respondents tend to have 1-10 plants and spend around <100 K (IDR) monthly to maintain and buy plants. They think that efforts to maintain were the most challenging in gardening activities. The majority of the respondents had potted plants at home to make their homes greener. The Kruskal Wallis test showed theÃÂ p-valueÃÂ (>0.05) for all characteristic respondents. Thus, it can be concluded that there was no significant difference regarding the motivation to have planted during the Covid-19 pandemic from characteristic respondents.